Freedom of speech, the right to privacy, defamation or misconduct: what rights do employees have when making workplace-related statements on social networking websites, and what of the rights of the employer? a critical analysis of legislation and case law, both in South Africa and internationally - Simoes, Caroline (Centre for Law and Society, 2026)
The rapid global expansion of social networking, and its impact in the workplace, is leading to increasing pressure on both employers and employees to monitor and manage their interactions on such media more carefully, in order to protect the employment relationship, and both individual and company reputations in the. wider public arena. The purpose of this paper is to critically analyse the rights of both employers and employees with regards to comments and statements made on social networking sites, particularly with regards to the potential impact of such statements in the workplace. The paper will assess the tension between the individual's rights to freedom of speech and privacy, as compared to the employer's right not to be defamed, or for its employees to commit misconduct in the workplace. This analysis will consist of an assessment of both the South African and international situation including the United States of America, United Kingdom, Australia, New Zealand and Canada; by critically analysing legislation, case law and other literature on the topic relating to these particular geographical regions. The result of the research shows that there is a complex interplay between the relevant individual and employer rights, and that the courts will be required to assess all of the facts in totality in relation to a given matter in order to determine whether or not a dismissal for comments made via social media is fair. This will include an assessment of the risks posed to both parties, including breach of employee privacy rights, through the illegitimate accessing of their postings, as well as the risk to employers of vicarious liability, for actions by their employees during the scope of their employment which may negatively impact third parties. On this basis the paper will recommend that employers implement clear and detailed policies with regards to the usage of social networking sites in, or related to, the workplace; and that employees utilize other mechanisms available to them for airing frustrations and grievances, such as, internal grievance procedures and employee assistance programmes; in order not to be found guilty of misconduct based on comments made via social networking media.